Amendment Properties Affect Crop Performance, Leaf Tissue Nitrogen, and Soil Nitrogen Availability Following Soil Treatment by Anaerobic Soil Disinfestation - Shrestha, Utsala; Swilling, Keagan J.; Butler, David M. (Frontiers in Sustainable Food Systems, 2021)
Efficacy of anaerobic soil disinfestation (ASD) for soilborne plant pathogen suppression is strongly influenced by soil environment and organic amendment attributes. At the same time, these factors influence soil nutrient availability, crop nutrition, and crop performance, but published information on ASD amendment property effects, including carbon to nitrogen (C:N) ratio and C substrate bioavailability, on crop performance and soil nutrient availability is limited. We evaluated ASD amendment effects on soil N availability, crop N status, and solanaceous crop performance in a series of trials: (1) greenhouse/growth chamber study of amendments (primarily molasses/soybean hulls and wheat bran) formulated at 10:1, 20:1, 30:1 and 40:1 C:N ratios (4 mg C g−1 soil), (2) field study with molasses/soybean hull-based amendments at equivalent C:N ratios/C rates (3) on-farm study with molasses/soybean hull-based amendments (4 mg C g−1 soil) compared to grower-standard control, and (4) field study of labile to recalcitrant amendment substrates at 30:1 C:N ratio ( 3.4 mg C g−1 soil). ASD amendment C:N ratio strongly influenced soil inorganic N and the lowest (10:1) ratio was associated with highest soil inorganic N at ASD treatment termination in both trials 1 and 2, which often persisted into the cropping phase. Accordingly, the lowest amendment C:N ratio was also associated with the highest biomass (trail 1), leaf tissue N (trial 2), and crop yield (trials 1, 2) among treatments, even with application of recommended fertigation rates to all treatments in the field study. In trial 3, ASD treatment induced higher soil inorganic N and crop yield than the control, but no differences were observed in plant tissue N. In trial 4, more decomposable ASD substrates reduced soil inorganic N at ASD treatment termination, with the highest soil inorganic N associated with the most recalcitrant amendment, but there was no effect on crop yield. ASD amendment C:N ratio, and to a lesser extent, amendment decomposability, exert a strong influence soil inorganic N and crop performance. Optimization of ASD treatments for disease management will require simultaneous optimization of crop nutrition practices to facilitate more holistic, less confounded assessment of crop performance and to facilitate recommendations for grower adoption.